Prevalence and risk factors of hypertension among clients seeking care at Selected Healthcare Facilities in Kenya - Jasmit Shah; Soraiya Manji; Cynthia Smith; Jamila Nambafu; Anthony Ochola; Linda Barasa; Faraj Amir; Husni Abdalla; Simeon Jowi; Caroline Mithi; Rajiv Patel; Sayed K. Ali (PLoS ONE, 2025)
Background Hypertension remains one of the primary risk factors for cardiovascular disease and the leading cause of mortality worldwide. According to the World Health Organization (WHO), as estimated 1.28 billion adults suffer from hypertension worldwide and approximately half are unaware of the problem. This study aimed to explore the prevalence of hypertension, and the association of sociodemographic, behavioral, and physiological factors related to hypertension in patients seeking care at the different healthcare facilities in Kenya. Methodology We carried out a cross-sectional survey study between April 2023 and July 2023. The general adult public visiting the outpatient clinics were recruited from 8 healthcare facilities in Kenya. Summary statistics were presented as medians and interquartile ranges for continuous data and frequencies and percentages for categorical data. The non-parametric Kruskal–Wallis test was used to compare the continuous variables and Fisher’s exact test was used to compare the categorical variables between group associations. Results A total of 1444 clients were recruited and included in the analysis. The median age of participants was 47.0 years, 54.3% were females, 75.1% were married and 42.9% reported living in the rural areas. The prevalence of hypertension was found in 29.4% of clients, of which 48.5% lacked awareness of their diagnosis. Of the patients who knew of their diagnosis (n = 412), 53.1% did not achieve blood pressure control as defined by Joint National Committee on prevention, detection, evaluation, and treatment of high blood pressure. Of note, 39.1% of participants with hypertension were from faith-based health facilities, 31.5% were from public institution and 29.4% were from private institutions (p < 0.001). In rural areas, faith-based facilities are the dominant care providers. Type of facility, age, gender, education, marital status, body mass index and residence were associated with hypertension (p < 0.05). Conclusion The study highlights a significant burden of hypertension among adults attending outpatient clinics in Kenya. Nearly half of hypertensive individuals were unaware of their condition, and among those diagnosed, more than half did not achieve target blood pressure levels, indicating gaps in screening, awareness, and management. These findings emphasize the need for targeted interventions, including improved screening, awareness campaigns, and enhanced treatment strategies to improve hypertension control in diverse healthcare settings.